2017
DOI: 10.1002/2016wr020195
|View full text |Cite
|
Sign up to set email alerts
|

Geological entropy and solute transport in heterogeneous porous media

Abstract: We propose a novel approach to link solute transport behavior to the physical heterogeneity of the aquifer, which we fully characterize with two measurable parameters: the variance of the log K values (r 2 Y), and a new indicator (H R) that integrates multiple properties of the K field into a global measure of spatial disorder or geological entropy. From the results of a detailed numerical experiment considering solute transport in K fields representing realistic distributions of hydrofacies in alluvial aquife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 91 publications
(162 reference statements)
10
71
0
Order By: Relevance
“…However, the value in case 1 with faster finger flow is much smaller than that in case 2 with a slower volume-averaged manner. The results are consistent with the conclusion of Bianchi and Pedretti [43] that fingering is more pronounced when the relative entropy is low. Therefore, in a way similar to the derivation of geological entropy indicators, it can be recognized that the relative entropy , which takes into account the spatial distributions of the heterogeneous fracture network including connectivity, extent and spacing, and aperture distribution, has significant effects on the development and propagation of preferential flow during heterogeneous seepage analysis.…”
Section: Preferential Flow Modelsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the value in case 1 with faster finger flow is much smaller than that in case 2 with a slower volume-averaged manner. The results are consistent with the conclusion of Bianchi and Pedretti [43] that fingering is more pronounced when the relative entropy is low. Therefore, in a way similar to the derivation of geological entropy indicators, it can be recognized that the relative entropy , which takes into account the spatial distributions of the heterogeneous fracture network including connectivity, extent and spacing, and aperture distribution, has significant effects on the development and propagation of preferential flow during heterogeneous seepage analysis.…”
Section: Preferential Flow Modelsupporting
confidence: 82%
“…It is found that the indicator is sensitive to the connectivity of the fracture networks. Furthermore, Bianchi and Pedretti [43] pointed out that is a global metric that integrates multiple properties of the spatial distribution of hydraulic conductivity.…”
Section: Preferential Flow Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the Shannon entropy H can be seen as a measure of unpredictability, it has been extensively applied to quantify uncertainty, disorder, and randomness in a wide range of disciplines, including hydrogeology, geostatistics, and related fields (e.g., Chiogna et al, ; Journel & Deutsch, ; Kitanidis, ; Mays et al, ; Ye et al, ). In Bianchi and Pedretti (), numerical simulations of solute transport in generic alluvial aquifers with a wide range of heterogeneity ( σlnK2 between 1.7 and 28.0, mean lengths of the facies between 1 and 30 m) were performed to analyze the effect of spatial disorder on the first three spatial central temporal moments of the breakthrough curves (BTCs). Empirical expressions were subsequently developed to describe the correlation between H R and these moments.…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, a detailed characterization of depositional facies is a valuable tool in order to identify and group together the geological and hydrogeological features of the system, possibly interacting with the contaminants (e.g. Bianchi and Pedretti 2017). For example, the occurrence in the stratigraphic architecture of organic-rich layers (such as peaty layers), could substantially affect the migration and degradation of contaminants, since the organic matter can sorb the contaminants and also act as electron donor in biodegradation reactions with potential production of hazardous metabolites (e.g.…”
Section: Introductionmentioning
confidence: 99%